Bandwidth Analysis of Bootstrap Transimpedance Amplifier for Optical Free Space Receiver - Idrus, S. M.; Rais, S. S.; Ramli, A. (Faculty of Electrical Engineering, 2008)
Free Space Optic (FSO) or optical wireless link operates in high noise environments. On the other hand, the performance is subjected to several atmospheric factors like environmental temperature, fog, smoke, haze and rain. Signalto-noise ratio (SNR) can vary radically with the distance and ambient noise. A good sensitivity and a broad bandwidth will habitually use a small photodetection area where the aperture is small. However, FSO optical receiver requires a large aperture and accordingly, to have a large collection area, which possibly will be achieved by using a large area photodetector and large filter. Consequently, large area photodetector produces a high input capacitance that will be reduced the bandwidth. Hence, techniques to reduce the effective detector capacitance are required in order to achieve a low noise as well as wide bandwidth design. In this paper, modeling and analysis of the series and shunt with floating source: and seriesshunt bootstrap transimpedance amplifier (BTA) of front-end receiver for input capacitance reduction will be presented. The result shows that the technique improved the conventional transimpedance amplifier (TIA) bandwidth up to 1000 times with an effective capacitance reduction technique for optical wireless detector